Cost-effectiveness of an adjustment group for people with multiple sclerosis and low mood: a randomized trial. (November 2013) - Humphreys, Ioan; Drummond, Avril ER; Phillips, Ceri; Lincoln, Nadina B
Objective: To evaluate the cost effectiveness of a psychological adjustment group shown to be clinically effective in comparison with usual care for people with multiple sclerosis. Design: Randomized controlled trial with comparison of costs and calculation of incremental cost effectiveness ratio. Setting: Community. Participants: People with multiple sclerosis were screened on the General Health Questionnaire 12 and Hospital Anxiety and Depression Scale, and those with low mood were recruited. Interventions: Participants randomly allocated to the adjustment group received six group treatment sessions. The control group received usual care, which did not include psychological interventions. Main measures: Outcomes were assessed four and eight months after randomization, blind to group allocation. The costs were assessed from a service use questionnaire and information provided on medication. Quality of life was assessed using the EQ-5D. Results: Of the 311 patients identified, 221 (71%) met the criteria for having low mood. Of these, 72 were randomly allocated to receive treatment and 79 to usual care. Over eight months follow-up there was a decrease in the combined average costs of £378 per intervention respondent and an increase in the costs of £297 per patient in the control group, which was a significant difference ( p =0.03). The incremental cost-effectiveness ratio indicated that the cost per point reduction on the Beck depression inventory–II was £118. Conclusion: In the short term, the adjustment group programme was cost effective when compared with usual care, for people with multiple sclerosis presenting with low mood. The longer-term costs need to be assessed.